Constitutional government in Sri Lanka - Cooray, L. J. M. (L. J. Mark) (Colombo, Sri Lanka : Lake House Investments, 1984)
Study covers the period 1976-1977.
Revision of the authorʼs thesis (Ph. D.--University of Colombo, 1979)
Includes index.
Keywords: Constitutional history -- Sri Lanka; Constitutional law -- Sri Lanka